Motion Structures Deployable Structural Assemblies of Mechanisms - You, Zhong (Taylor & Francis, 2012)
Motion structures are simply assemblies of resistant bodies connected by movable joints. Unlike conventional structures, they allow large shape transformations to satisfy practical requirements and they can be used in:shelters, emergency structures and exhibition standsaircraft morphing wingssatellite solar panels and space antennasmorphing core ma